Generosity and support fund - Qodirova Mamlakat Mominovna (Genius Publishing Group, 2023)
This article explains that generosity, kindness, helping each other is an ancient value for the Uzbek people, and therefore the Foundation "Generosity and Help" was established. Explanations about the purpose of this fund, its tasks, and the public fund are given.
Keywords: generosity; kindness; national traditions